Efficacy of concentration of egg yolk in Tris extender with and without seminal plasma on frozen semen quality of Saanen bucks - Tambing, Surya Natal; Sutama, I-K; Sariubang, M (Indonesian Animal Sciences Society, 2008)
Bucks semen is easily damaged compared to bull semen during cryopreservation process. Consequently, frozen semen quality decrease especially motility, live sperm, intact plasma membrane, and intact acrosomal cap after thawing. Objectives of this research was to evaluate the effect of egg yolk concentration in Tris extender with and without seminal plasma in maintaing frozen semen quality of Saanen buck. Four heads of Saanen buck of 2-4 years old were used in this experiment. Semen was collected once a week using artificial vagina. Experimental design applied was factorial complete random desing 2x2, viz. A factor was seminal plasma (A1 = with seminal plasma and A2 = without seminal plasma), and B factor was concentration of egg yolk (B1 = 10% and B2 = 20%). Duncan test were applied to identity differences between treatment. Result of these study indicated that the mean percentage of motility (M), live sperm (LS), sperm with intact plasma membrane (IPM) and intact acrosomal cap (IAC) after dilution and equilibration were not significantly different (P>0.05) in all treatment. After thawing, the mean percentage of M, LS sperm with IPM and IAC in A1 treatment (41.43, 51.52, 56.63 and 50.35% respectively) were significantly higher (P<0.05) than A2 treatment (37.14; 48.67; 52.31 and 45.09% respectively). Likewise, the mean percentage of M, LS, sperm with IPM and IAC in B2 treatment (41.79; 51.32; 55.78 and 49.50% respectively) were significantly higher (P<0.05) than B1 treatment (36.79, 48.86; 53.16 and 45.94% respectively). There were a significant interaction between factors of seminal plasma and concentration egg yolk in Tris extender, where the increase of egg yolk concentration from 10% to 20% in unwashed seminal plasma treatment caused increase in percentages of M, LS, sperm with IPM and IAC. On the other hand in washed seminal plasma treatment there were a trend of decreasing frozen semen quality. It is concluded that the combination of 20% egg yolk in Tris extender with seminal plasma is effective in maintaining frozen semen quality of Saanen bucks. Key Words: Saanen Bucks, Semen Quality, Egg Yolk, Seminal Plasma